Upaya Peningkatan Pengetahuan Kesehatan Gigi dan Mulut di SDN Runduma, Wakatobi, Sulawesi Tenggara (VDE 3) - Azwinda Arli; Dwi Aji Nugroho; Sartika Puspita (Fakultas Kedokteran Gigi, Universitas Jember, 2024)
Oral and dental health maintain, requires serious attention in Indonesian. The 5-9year age group has the greatest dental and oral health problems and only 1.4% have the habit of brushing their teeth at the right time. Primary school age children are in the mixed dentition phase, so they are very susceptible to caries. At this age, children need to be equipped with the right knowledge and skills, character formation will be greatly influenced by information and habits from the environment. Barakati Indonesia through the Village Development Expedition (VDE 3) held a service on Runduma Island, which is a small island located at the easternmost point of Wakatobi Regency. The VDE 3 program is an interdisciplinary program that aims to develop underdeveloped villages. Health division of VDE 3 carries out dental health education efforts for students at Runduma primary School to create healthy habits, especially in maintaining dental and oral health. The results of the dental health education show an increase in the dental and oral health knowledge of the students in Runduma primary school based on the average score from the pre-test and post-test that was held. Correct tooth brushing techniques are trained after dental anda oral health promotion. Community service activities was aimed to improve dental and oral health among Runduma primary School students were carried out well.Keywords: dental and oral health, volunteer, health promotion.